Scott, Hilton 2022. A Sense of Belonging:: Being Church in a Pluralistic Society. Eugene, OR: Resource Publications. - Cones, Bryan (Stellenbosch Theological Journal, 2024)
The challenges of bridging the cultures and differences of church members are among the most pressing concerns congregations face in urban pluralistic cultures. Add to this a history of oppression and injustice based on race, as one might find in the author’s country of South Africa or in this reviewer’s home in United States of America, and the work becomes decidedly more urgent. One hopes the common prayer that unites congregations, sustained by the personal spiritual practices of members, might support bridges to cross that divide. But how?